Demographic and Clinical Profile of Juvenile Idiopathic Arthritis Patients in a Tertiary Referral Hospital in Indonesia (2021–2023) - Callista Nadhifa Parama Satwika; Azwin Mengindra Putera; Deasy Fetarayani; Taufiq Hidayat (Universitas Airlangga, 2026)
Background: Juvenile Idiopathic Arthritis (JIA) is the most common chronic rheumatic disease in children, characterized by joint inflammation lasting ≥6 weeks in individuals aged <16 years without a clear etiology. Despite advances in research on genetic, immunological, and environmental factors, its pathogenesis remains incompletely understood. In Indonesia, epidemiological data and clinical characteristics of JIA are still limited. This study aimed to describe the demographic profile and clinical characteristics of JIA patients at the pediatrics outpatient clinic of a tertiary referral hospital in Indonesia from 2021 to 2023.Methods: A descriptive retrospective study was conducted to evaluate medical records of patients who met the diagnostic criteria for JIA based on the International League of Associations for Rheumatology (ILAR) classification.Results: Of the 73 JIA patients, most were male (60.3%) and belonged to the age group >132–216 months (32.9%). Most patients were domiciled in Surabaya (35.6%). The most common chief complaint was joint pain (71.2%), and 58.9% had joint involvement involving <5 joints, suggesting an oligoarthritis subtype. Most patients’ vital signs were within normal limits, while anemia (58.9%) and elevated erythrocyte sedimentation rate (ESR) (80.8%) were the dominant laboratory findings.Conclusion: The majority of JIA patients were late-adolescent boys (132–216 months) presenting with pain and an oligoarthritis subtype. These findings highlight the importance of early detection and appropriate referral to prevent long-term complications.